Introduction to Islamic Entrepreneurship at an Early Age for Children at the Ummu Aiman Aisyiyah Orphanage, Mamajang Branch, Makassar City - M. Yusuf K; Nasrullah; Syahidah Rahmah; Muhammad Fatir Hidayat; Ifan Prastia (www.amertainstitute.com, 2025)
Embedding Islamic entrepreneurship values from an early age plays a crucial role in shaping children's character and mentality, preparing them to face future economic challenges. Islamic entrepreneurship education not only teaches business skills but also instills strong ethics and morals. Teaching entrepreneurship from an early age helps children develop creativity, innovation, and independence—important qualities in the business world. It also cultivates resilience and risk management abilities, key factors for success in entrepreneurship. Islamic entrepreneurship emphasizes operating businesses with honesty, fairness, and responsibility. Children who learn these values early will grow into entrepreneurs who achieve financial success with high integrity and ethics. They will understand that profit is not the sole objective of business but also the benefit it brings to society and the environment. Additionally, entrepreneurship education helps children avoid consumerist habits by understanding the production process and appreciating the value of goods. Through entrepreneurial activities, they will also develop social and communication skills. This study aims to introduce Islamic entrepreneurship to children at the Ummu Aiman Aisyiyah Orphanage, Mamajang Branch, Makassar City, fostering economic independence and encouraging entrepreneurship driven by both profit and spiritual fulfillment.